Pattern of gp120 sequence divergence linked to a lack of clinical progression in human immunodeficiency virus type 1 infection. - Wang, W K (1996)
Differential rates of AIDS development and/or T4 lymphocyte depletion in HIV-1-infected individuals remain unexplained. The hypothesis that qualitative differences in selection pressure in vivo may account for different rates of disease progression was addressed in nine eligible study participants from a cohort of 315 homosexual men who have been followed since 1985. Disproportionately fewer changes in variable regions and more in C3 of gp12O were found to be significantly associated with slower disease progression. Our finding provides the first example to demonstrate that differential selection pressure related to the emergence of HIV-1 variants is associated with long term nonprogression. Candidate vaccines that elicit strong selection pressure on C3 of gp120 are likely to provide better protection than those targeting variable regions.